2018
DOI: 10.1002/jcc.25712
|View full text |Cite
|
Sign up to set email alerts
|

RPA(D) and HRPA(D): Two new models for calculations of NMR indirect nuclear spin–spin coupling constants

Abstract: In this article, the RPA(D) and HRPA(D) models for the calculation of linear response functions are presented. The performance of the new RPA(D) and HRPA(D) models is compared to the performance of the established RPA, HRPA, and SOPPA models in calculations of indirect nuclear spin–spin coupling constants using the CCSD model as a reference. The doubles correction offers a significant improvement on both the RPA and HRPA models; however, the improvement is more dramatic in the case of the RPA model. For all co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 65 publications
4
30
0
Order By: Relevance
“…On the other hand the savings in computation time are much larger and more consistent with the RPA(D) method, as also observed in Ref. . The implementation of triplet excitation energies with the doubles corrected methods enabled the further implementation of nuclear spin–spin coupling constants which is also presented in Ref.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…On the other hand the savings in computation time are much larger and more consistent with the RPA(D) method, as also observed in Ref. . The implementation of triplet excitation energies with the doubles corrected methods enabled the further implementation of nuclear spin–spin coupling constants which is also presented in Ref.…”
Section: Discussionsupporting
confidence: 68%
“…The implementation of triplet excitation energies with the doubles corrected methods enabled the further implementation of nuclear spin–spin coupling constants which is also presented in Ref. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLEASE CITE THIS ARTICLE AS DOI:10.1063/5.0002389 (SOPPA) 5 has proven very useful, as it yields results in good agreement with experiment, while being computationally less demanding than the high-accuracy Coupled Cluster (CC) methods 6 . For larger systems of more than roughly 30 atoms or 800 basis functions, however, even SOPPA can be rather time consuming, wherefore cheaper, but also less reliable alternatives are available such as RPA 7,8 , RPA(D) [9][10][11] , HRPA 12 and HRPA(D) 9,10 . In addition to the abovementioned methods, a range of TDDFT methods are also available 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The second study [28] extended the first study and tested the two precursors to SOPPA, the random phase approximation (RPA) and the higher order random phase approximation (HRPA) as well as the two new, doubles corrected methods, RPA(D) and HRPA(D). These two newer methods were originally derived for the calculation of excitation energies [43–45] and NMR spin–spin coupling constants [46] and were in the previous study [28] extended to the calculation of polarizabilities. Surprisingly it was found that the relatively more simple model, RPA, performed closer to CC3 than SOPPA for both static and dynamic polarizabilities.…”
Section: Introductionmentioning
confidence: 99%